Constructing halitosis sensor for early detection in periodontal diseases - Nurlindah Hamrun; Filzah Azalia; Nurul Auliya; Muhammad Riswan (DiscoverSys Inc., 2020)
Objective: The purpose of this research is to create a halitosis sensor device that can detect periodontal disease through bad breath.Material and Methods:The method used is MQ 136 gas sensor which possesses high sensitivity to H2S gas and can monitor organic vapor including sulfur well.Results: The result of the resistance value obtained in the sensor is changed to the concentration value of the substance and displayed inÂ the LCD. When the power button is switched on then the power supply from the battery is flowing in the Arduino and LCD. When the â€œresultâ€ button is pressed it will appear the desired result on the LCD in the form of H2S element concentration and also predicted the status of periodontal disease suffered by the patient.Conclusion:This halitosis sensor can detect early periodontal disease experienced by a person so that patients with a suspected periodontal disease can be treated as soon as possible.